Opisthonema bulleri ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
? Opisthonema bulleri (Regan, 1904). Slender Thread Herring. To 24 cm (9.4 in) TL (Robertson and Allen 2015). Several specimens taken south-east of Punta Abreojos, southern Baja California (Jason Masters, photographs to M.L., tentatively confirmed by Ross Robertson); Gulf of California to northern Peru (Robertson and Allen 2015). Depth: intertidal to perhaps 10 m (33 ft) (min.: Personal communication: Scripps Institution of Oceanography Fish Collection, La Jolla, California; max.: Robertson and Allen 2015). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 44, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...